An Automatic Drilling and Riveting Robot based on 3-RPC/6-UPS Parallel Mechanism - Zhe Qin; Shoushuai Jiang (Jixie chuandong)
An automatic drill and riveting robot based on 3-RPC/6-UPS parallel mechanism is proposed to complete the drilling and riveting task of aircraft panel. The robot is equivalent to be a fixed parallel machine tool when performing drilling and riveting， and it also can be seen as a standing robot while walking. The inverse kinematics model of 6-UPS parallel mechanism in charge of controlling the robot drilling and riveting actuator is established. The working space for the end of drilling and riveting actuator is obtained by numerical search method. The inverse kinematics model of 3-RPC parallel mechanism in charge of controlling the robot walking is established. The working space of the upper and lower platform of the 3-RPC parallel mechanism is drawn by numerical search method. The displacement trajectory of the driving rod controlling the robot walking is planned by quintic polynomials， and the smooth walking of the robot prototype is realized in the virtual software. The research work could lay a theoretical foundation for the design of a new type of mobile robot for large-scale structural parts processing.